Stem cells for the treatment of neurodegenerative diseases - Dantuma, Elise (BioMed Central, 2010)
Stem cells offer an enormous pool of resources for the understanding of the human body. One proposed use of stem cells has been as an autologous therapy. The use of stem cells for neurodegenerative diseases has become of interest. Clinical applications of stem cells for Alzheimer disease, Parkinson disease, amyotrophic lateral sclerosis, and multiple sclerosis will increase in the coming years, and although great care will need to be taken when moving forward with prospective treatments, the application of stem cells is highly promising.